Utilization of Lime Fines as an Effective Binder as well as Fluxing Agent for Making Fluxed Iron Ore Pellets - Mandal A.K.; Sarkar A.; Sinha O.P. (My University, 2025)
A laboratory study was carried out to characterize the physical, chemical and mechanical properties of lime fluxed (varying basicity 0–2) hematite iron ore pellets. Lime was used as additive as well as fluxing agent for making iron ore pellets. The effect of additives on different properties of pellets was studied. The findings show that on increasing the addition of lime, more of calcium-alumino-silicate phases were produced as confirmed by SEM-EDAX analysis. These phases have low melting points, which enhances sticking behaviour of pellets, as well as imparts strength to the pellets (resulting increasing compressive strength, tumbler, abrasion and shatter index) but decreases the porosity. The low basicity pellets were found predominantly oxide-bonded, while the high basicity pellets were mostly slag-bonded. This means that the pellet should be fired at sufficiently high enough temperature to generate liquid phases to get the sufficient strength but not so high as to cause the pellets to stick to each other. The obtained properties of these fluxed pellets were compared with the properties of iron ore lump and pellets, which are being used conventionally in the blast furnace for production of iron and steel. © 2015, The Institution of Engineers (India).